Coincidencias léxicas entre el español de Canarias y el de la península de Yucatán - Pérez Aguilar, Raúl Arístides (El Colegio de México, 2016)
Fecha de recepción: 23 de noviembre de 2015.Fecha de aceptación: 22 de abril de 2016. An analysis is made of several words taken from the Tesoro lexicográfico del español de Canarias by Corbella, Corrales and Álvarez, and from the Diccionario del español yucateco by Güemez, that appear to be usual forms of expression in both the canary Islands and the Yucatecan Peninsula. An attempt is made to detect semantic coincidences between words. These coincidences are then commented in the light of results of a series of surveys carried out in Merida, Chetumal and Campeche in 2015. reference is also made to other works in an effort to establish their geolectal distribution in the region.